Empowering the 'Sanggah Jiwa' Community: Optimizing Nature-Based Mental Health Support and Earthing to Reduce Youth Depression - Elsy Junilia; Akhmad Kheru Dharmawan; Adhitya Anata Bakti (UKInstitute, 2026)
Depression among adolescents and young adults is a critical mental health issue, yet it is often hindered by stigma and limited access to formal services. The village of Lempasing possesses significant natural resources that have not yet been fully utilized to support the psychological well-being of its community. Objective: This community service (PkM) activity aims to empower local cadres through the formation of the “Sanggah Jiwa Community” and to implement nature-based interventions to reduce depression rates among young people. Methods: The program was implemented using a community empowerment approach that included mental health literacy training, the development of mentoring modules, and four weeks of field practice involving Nature Exposure and Earthing (direct contact with the earth) interventions. A total of 15 community leaders were trained, and 30 adolescents with depressive symptoms participated. The effectiveness of the intervention was measured using the Patient Health Questionnaire-9 (PHQ-9) through pre-test and post-test assessments. Results: The findings demonstrated an increase in the community leaders’ capacity to conduct peer-to-peer support independently. Quantitative data analysis showed a significant decrease in PHQ-9 scores among adolescent participants post-intervention (p < 0.05). Conclusion: Empowering local communities through nature-based interventions has proven effective as a low-cost, sustainable, and complementary solution to address depression issues at the